Governance Systems and Municipal Governing—One City's Experience. Issue 157 (May 2018) - Lewis, Rob
Abstract : Rob Lewis currently serves as program coordinator with the City of Red Deer, Alberta, Canada. He has a diploma in theology from Vanguard College, Edmonton, Alberta, and is certified in Policy Governance proficiency. In this article, he looks at the unique challenges and solutions related to implementing Policy Governance in a municipal council environment in Red Deer. It gives the history of the city's municipal governance and talks about why it looked to do something different, why it landed on Policy Governance, and the results the city has seen thus far.